2014
DOI: 10.1055/s-0034-1372248
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Prognostic Implications of Major Adverse Cardiovascular Events after Renal Transplant: 10 Years Outcomes in 321 Patients

Abstract: Renal transplantation is the treatment of choice in patients with end-stage renal disease. Major adverse cardiac events (MACE) are common after renal transplant, especially in the perioperative period, leading to excess morbidity and mortality. The predictors and long-term prognostic implications of MACE are poorly understood. We analyzed predictors and implications of MACE in a cohort of 321 consecutive adult patients, who received renal allograft transplantation between 1995 and 2003 at our institution. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Following transplantation, the rates of MI remain high, with a cumulative risk of 6.5%11.1% at 36 mo, and the greatest burden of disease being seen in the first 6 mo posttransplant [22] . In fact, 86% of major adverse cardiac events occur within 180 d [23] . Other studies corroborate this pattern with prevalent CVD numbers at 20%, and 14% of RTRs having a previous MI [24] .…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Following transplantation, the rates of MI remain high, with a cumulative risk of 6.5%11.1% at 36 mo, and the greatest burden of disease being seen in the first 6 mo posttransplant [22] . In fact, 86% of major adverse cardiac events occur within 180 d [23] . Other studies corroborate this pattern with prevalent CVD numbers at 20%, and 14% of RTRs having a previous MI [24] .…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…The incidence of myocardial infarction following transplantation is still high (6.5–11.1% at 36 months) and reaches its peak within the first 6 months from the procedure [ 141 ]. Aftab et al [ 142 ] revealed that 86% of major adverse cardiac events occurred within the first 180 days. Moreover, it has been demonstrated that the development of post-transplant diabetes worsens graft function which in consequence leads to enhanced morbidity and mortality, especially from CV events [ 6 ].…”
Section: Cardiovascular Risk and Morbidity Of Renal Transplant Patmentioning
confidence: 99%